Evaluation of Colonoscopy Screening Results in the First-Degree Relatives of Patients with Familial Colorectal Cancer X-Type - SH Abedi Valukalaie (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Colorectal cancer is one of the growing cancers in Iran and one of the few preventable cancers in the World Health Organization. One of the most important ways to early diagnose this malignancy and its underlying lesions (polyps) and subsequently to prevent it is screening. Colorectal cancer is one of the growing cancers in Iran and one of the few preventable cancers in the World Health Organization. One of the most important ways of early detection of this malignancy and its underlying lesions (polyps) and consequently its prevention is screening. Different protocols have been developed for the diagnosis of first degree relatives of known hereditary cases such as HNPCC and FAP, but the diagnosis plan for first degree relatives has not been defined as a group of familial colorectal cancers without known mutations (type X colorectal cancer). The purpose of this study was to evaluate the results of colonoscopy screening in first-degree relatives of these patients. METHODS: This cross-sectional study was performed on the families of patients with suspected Lynch syndrome who had no deficiency in the expression of repair proteins. Data were collected from the medical records system of colorectal cancer patients who had been enrolled in the system for prevention and early detection of colorectal cancer at Shahid Beheshti University of Medical Sciences Research Center from 1387 to 1397. FINDINGS: The results of colonoscopy revealed that 18 out of 77 subjects had 23% polyps or tumors in their colon, out of which 55% were polyps and the rest were adenomas. About 60% of polyps were in the rectum and sigmoid and the rest in the colon and cecum. Also, 4 patients in this screening showed tumors in their colon, all of which were newly diagnosed, and 2 patients in this screening were diagnosed with inflammatory bowel disease. CONCLUSION: According to the results of this study, in the case of colon polyps, the families of these patients appear to be at high risk like those of Lynch syndrome families and need regular colonoscopy care.